Fundamental of aerodynamics - Anderson, John David (McGraw-Hill series in aeronautical and aerospace engineering, 2001)
In keeping with previous editions, Fundamentals of aerodynamics, Third edition offers the most readable, interesting, and up-to-date overview of aerodynamics to be found in any text.